Analisis Finansial dan Nilai Tambah Pengolahan Kopi Arabika di Koperasi Tani Manik Sedana Kabupaten Bangli - NI LUH MADE INDAH MURDYANI DEWI; I WAYAN BUDIASA; IDA AYU LISTIA DEWI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2015)
ABSTRACT Financial Analysis and Added Value Manufacturing of Arabica Coffee at Farm Cooperative of Manik Sedana Bangli Regency The study aims to analyze added value and feasibility study of Arabica Coffee manufacturing at Farm Cooperative of Manik Sedana. Survey method was used to gather primary data from five persons of management board of the company. Secondary data related to this study were collected from appropiate sources. The added value for one production cycle was accounted by using Hayami et al method and feasibility study implemented discounted criteria (NPV, IRR, Net B/C and sensitivity analyze) during the 10 years as economic life of project on rate 6% . The process from fresh to HS coffee and from fresh to powder coffee yielded additional value of IDR 1,875.05 and IDR 6,642.34 per kilogam fresh coffee. Based on investment criteria, the processing of Arabica Coffee was financially feasible indicated by NPV = IDR 667,757,620; IRR = 28.70%; Net B/C = 2.00 . The Bussiness will be financially infeasible if both HS and powder coffee prices decreased. Key Words: value added, feasibility, manufacturing of arabica coffee